Phonological Adaptation of English Pseudo-loanwords (Wasei Eigo) in Japanese - Ariefandi, Febryan; Hariri, Tatang (STKIP PGRI Ponorogo Press, 2024)
Some researchers have classified wasei eigo, a unique phenomenon in the absorption of English words into Japanese, as pseudo-loanwords. These words are notable for their characteristics, which not only change morphologically but also semantically. However, the phonological adaptation that occurs in English words when they are absorbed into wasei eigo is often ignored by some researchers. In fact, understanding this adaptation needs to be deepened first, considering English has a different phonological system from Japanese. This study aims to fill the gap by examining wasei eigo words found in Japanese online communication, especially on social media. The purpose of this study is to explain the phonological processes and rules of wasei eigo. Based on data findings, analyzed using both the theory of English and Japanese phonological systems, Japanese tend to adapt English words by adding, deleting, and substituting phonemes. Several reasons underlie these adaptations, including the absence of phonemes in the target language and differences in syllable systems. As a first step in analyzing the phenomenon of pseudo-loanwords in Japanese, this research will serve as a foundation to further study wasei eigo from various perspectives of linguistics.